PENGARUH TRANSFER PRICING, SALES GROWTH DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - Firdaus, Ahmad Amri; Wahyudi, Ilham; Herawaty, Netty (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
The purpose of this study was to determine and analyze the effect of Transfer Pricing, Sales Growth and Leverage on tax avoidance in energy sector companies listed on the IDX for the 2019-2022 period. This research is quantitative research. The type of data used is secondary data sourced from the Indonesia Stock Exchange (IDX) or the official website of each company. The population in this study amounted to 85 companies. The data collection method used was purposive sampling and obtained data for 17 companies. The analysis methods used are descriptive statistics, classical assumption tests, multiple linear regression and hypothesis testing. The result of this study is transfer pricing has a significant influence on tax avoidance. Meanwhile, sales growth and leverage have no significant effect on tax avoidance. Together transfer pricing, sales growth and leverage simultaneously affect tax avoidance.